Early vagus nerve stimulator implantation as a main predictor of positive outcome in pediatric patients with epileptic encephalopathy. Issue 4 (17th August 2021) - Russo, Angelo; Hyslop, Ann; Gentile, Valentina; Boni, Antonella; Miller, Ian; Chiarello, Daniela; Pellino, Giuditta; Zenesini, Corrado; Martinoni, Matteo; Lima, Mario; Ragheb, John; Cordelli, Duccio Maria; et al.
Abstract: Objective : We describe a multicenter experience with VNS implantation in pediatric patients with epileptic encephalopathy. Our goal was to assess VNS efficacy and identify potential predictors of favorable outcome. Methods : This was a retrospective study. Inclusion criteria were: ≤18 years at the time of VNS implantation and at least one year of follow‐up. All patients were non‐candidates for excisional procedures. Favorable clinical outcome and effective VNS therapy were defined as seizure reduction >50%. Outcome data were reviewed at one, two, three and five years after VNS implantation. Fisher's exact test, Kaplan‐Meier and multiple logistic regression analysis were employed. Results : Twenty‐seven patients met inclusion criteria. Responder rate (seizure frequency reduction ≥ 50%) at one‐year follow‐up was 25.9%, and 15.3% at last follow‐up visit. The only variable significantly predicting favorable outcome was time to VNS implantation, with the best outcome achieved when VNS implantation was performed within five years of seizure onset (overall response rate of 83.3% at one year of follow‐up and 100% at five years). In total, 63% of patients evidenced improved QOL at last follow‐up visit. Only one patient exited the study due to an adverse event at two years from implantation. Significance : Early VNS implantation within five years of seizure onset was the only predictor of favorable clinical outcome in pediatric patients with epileptic encephalopathy. Improved QOL and a very low incidence of adverse events were observed.